Strategi Mewujudkan Peningkatan Kinerja Pada BUMDes Segara Giri di Desa Sanur Kauh - Ida Bagus Udayana Putra; Ida Ayu Surasmi; I Made Wianto Putra (Postgraduated Community Service Journal, 2023)
Village-Owned Enterprises were established by Village communities in an effort to improve the Village economy through efforts to manage existing natural resources, social potential and economic potential. Therefore, it is necessary to manage Bumdes management professionally so that it is in accordance with its vision and mission. The success of the vision and mission can be determined by competent human resources who are committed to their duties and responsibilities. This service aims to improve performance at Bumdes Segara Giri in Sanur Kauh Village, starting with analyzing the village's potential for preparing a clear and focused business plan, managing production or service provision, marketing and promotion of products or services produced, regular financial management. as well as transparency as well as developing skills and increasing the capacity of human resources. This service begins with interviews and documentation methods with several sources and is supported by documentation. In terms of implementation, the principles of management have been carried out in accordance with the performance analysis of the BUMDes, but there is still a need for steps or strategies so that a good improvement in BUMDes performance can be achieved optimally. This condition is motivated by the limited understanding of human resources. The results of the service show that Bumdes Segara Giri generally has good performance such as providing quality service to the community and maintaining its sustainability, but there are inhibiting factors that require improvement efforts and recommendations to achieve good management.